Simulation of a Perforated Vertical Wellbore with Near Wall Porous Media Effect - Mohammed, Haider S.; Sultan, Hussein S.; Khazal, Emad A. (Journal of Petroleum Research and Studies, 2022)
This paper aims to predict the effect of porous media permeability and perforations parameters on the pressure drop and productivity index, for the perforated vertical wellbore with six perforations and for two phase angles. The first 60ᵒ phase angle with helical distribution and the second 180ᵒ phase angle with normal distribution. In this study, a Computational Fluid Dynamics (CFD) software has been used to simulate a model of 3-D turbulent fluid flow with stander k−∈, steady-state, and single phase. The effect of the permeability of porous media, inlet mass flow rate from porous media, perforations length, and diameter of perforations are studied, for two cases of the phase angles. The results of this study show that, the pressure drop decreases with increasing permeability pf porous media, so the productivity index increasing. Also, increase of inlet mass flow rate from porous media causing an increase in the pressure drop. The perforations length has a few effects on the pressure drop and productivity index, while the diameter of perforations has a greater effect on the pressure drop.